PIONEERING ADVANCEMENTS IN UROLOGY: ARTIFICIAL INTELLIGENCE, GENOMIC INSIGHTS, NOVEL TREATMENTS, DIAGNOSTICS, AND TARGETED THERAPIES TRANSFORMING PATIENT CARE - Gois, Breno Oliveira; Bento, Rodolpho Bicalho; Kastrup, Bianca Maria de Negreiros; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Recent advancements in urology are transforming patient care by integrating artificial intelligence (AI), genomic insights, and novel therapeutic approaches. This review explores the significant strides made in the field, particularly the application of AI in enhancing diagnostic precision and treatment strategies. The role of genomics in identifying molecular targets and pathways has enabled the development of targeted and personalized treatments, revolutionizing the management of urological disorders. We highlight novel pharmacological and non-pharmacological treatments that have shown efficacy in improving patient outcomes. Additionally, advancements in diagnostic methodologies, including non-invasive tests and precision imaging, have facilitated early and accurate disease detection. The review also addresses the emerging trends in biological therapies and the use of portable monitoring devices that support continuous care. By synthesizing current research, this article provides a comprehensive overview of the cutting-edge technologies and approaches that are setting the stage for future innovations in urology, aiming to enhance patient outcomes and optimize care delivery.